Sodium Houttuyfonate Ameliorates β-amyloid1-42-Induced Memory Impairment and Neuroinflammation through Inhibiting the NLRP3/GSDMD Pathway in Alzheimer's Disease - Yuequan Zhao; YunPeng Tian; Tao Feng (Hindawi Limited, 2021)
Objective. Our research is designed to explore the function of sodium houttuyfonate (SH) on Alzheimer's disease (AD) and its potential molecular mechanisms. Methods. In our study, the Morris water maze (MWM) test was used to assess the role of SH on spatial learning and memory deficiency in amyloid-β peptide (Aβ)1-42-induced AD mice. We explored the functions of SH on proinflammatory cytokines, neuron apoptosis, and damage in vivo and in vitro by using an enzyme-linked immunosorbent assay (ELISA), quantitative real-time polymerase chain reaction (qRT-PCR), flow cytometry, western blot, and Nissl staining. Moreover, the effect of SH on oxidative stress in vivo and in vitro was also detected. To explore the underlying molecular mechanisms of SH on AD, the expressions of proteins and mRNA involved in the NOD-like receptor pyrin domain containing-3/gasdermin D (NLRP3/GSDMD) pathway were determined using western blot, immunofluorescence staining, and qRT-PCR. Results. Our data demonstrated that SH ameliorated spatial learning and memory deficiency in Aβ1-42-induced AD mice. Moreover, SH significantly improved hippocampal neuron damage and inhibited oxidative stress, neuroinflammation, and neuron apoptosis in Aβ1-42-induced AD mice and PC12 cells. The results also revealed that SH protected Aβ1-42-induced AD through inhibiting the NLRP3/GSDMD pathway. Conclusion. The present study demonstrated that SH could ameliorate Aβ1-42-induced memory impairment neuroinflammation and pyroptosis through inhibiting the NLRP3/GSDMD pathway in AD, suggesting that SH may be a potential candidate for AD treatment.